If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x(x + 1) + 109 = x + (x + 1) Reorder the terms: x(1 + x) + 109 = x + (x + 1) (1 * x + x * x) + 109 = x + (x + 1) (1x + x2) + 109 = x + (x + 1) Reorder the terms: 109 + 1x + x2 = x + (x + 1) Reorder the terms: 109 + 1x + x2 = x + (1 + x) Remove parenthesis around (1 + x) 109 + 1x + x2 = x + 1 + x Reorder the terms: 109 + 1x + x2 = 1 + x + x Combine like terms: x + x = 2x 109 + 1x + x2 = 1 + 2x Solving 109 + 1x + x2 = 1 + 2x Solving for variable 'x'. Reorder the terms: 109 + -1 + 1x + -2x + x2 = 1 + 2x + -1 + -2x Combine like terms: 109 + -1 = 108 108 + 1x + -2x + x2 = 1 + 2x + -1 + -2x Combine like terms: 1x + -2x = -1x 108 + -1x + x2 = 1 + 2x + -1 + -2x Reorder the terms: 108 + -1x + x2 = 1 + -1 + 2x + -2x Combine like terms: 1 + -1 = 0 108 + -1x + x2 = 0 + 2x + -2x 108 + -1x + x2 = 2x + -2x Combine like terms: 2x + -2x = 0 108 + -1x + x2 = 0 Begin completing the square. Move the constant term to the right: Add '-108' to each side of the equation. 108 + -1x + -108 + x2 = 0 + -108 Reorder the terms: 108 + -108 + -1x + x2 = 0 + -108 Combine like terms: 108 + -108 = 0 0 + -1x + x2 = 0 + -108 -1x + x2 = 0 + -108 Combine like terms: 0 + -108 = -108 -1x + x2 = -108 The x term is -1x. Take half its coefficient (-0.5). Square it (0.25) and add it to both sides. Add '0.25' to each side of the equation. -1x + 0.25 + x2 = -108 + 0.25 Reorder the terms: 0.25 + -1x + x2 = -108 + 0.25 Combine like terms: -108 + 0.25 = -107.75 0.25 + -1x + x2 = -107.75 Factor a perfect square on the left side: (x + -0.5)(x + -0.5) = -107.75 Can't calculate square root of the right side. The solution to this equation could not be determined.
| 16t-15t=14 | | x=y-11 | | -3x-(-8x)=15 | | (8/125)-2/3 | | 5x-1+1x+15=6+5x+14-21 | | 19t-11t=16 | | -8x-7(-6x)=0 | | y=50+15x | | 9q-3q=6 | | -5h-3-7h=-171 | | 10+5u=-21 | | 2c-4=14c-10 | | 4(y+5)-y=35 | | a+(-1.6)=-3.7 | | 5+6=-16 | | 7q-6q=-18 | | 3v-24=-2(v+7) | | 3-2(x+5)=5(4x) | | 6m+(-m)=-20 | | 2+-2w=6 | | (70)=-8x-106 | | (5)=3x-7 | | 7x+58=3x+22 | | 2y-7=7 | | (14)=-4x+50 | | 7x+1=7x^2-1 | | 4/5x*(-2/10)=1 | | f+0.2=-3 | | kx^2+(k-3)x=1 | | (-80)=-1.3x+20 | | -2x+1=x+10 | | 4/5x(-2/10)=1 |